Improving Student Literacy Skills in Research and Scientific Articles: Arabic Language Education Study Program Sunan Kalijaga State Islamic University (2015-2020) - Huda, Nurul (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
Indonesian education is currently faced with low interest in literacy. The results of the latest study/research from The Program for International Student Assessment (PISA) in 2018, which was released on December 3 2019 by the Ministry of Education and Culture, stated that Indonesia was ranked 62nd out of 71 countries. This research aims to describe the efforts of the UIN SuKa Arabic Education study program in improving students' literacy skills in research and scientific articles. This research is descriptive qualitative research. Data collection was carried out using observation and documentation methods. The data obtained will be analyzed using the Miles and Huberman model through three stages: data reduction, data display, then data conclusion drawing. The results of this research indicate that in the UIN SuKa Arabic Education study program's efforts to improve students' literacy skills in scientific articles, it can be viewed from three things, (1) viewed from classroom learning, (2) viewed from activities outside the classroom and (3) efforts others obtained independently by students. Viewed from classroom learning, the efforts made are (1) assistance in writing scientific articles, (2) motivating students. Viewed from learning outside the classroom, the efforts made are (1) developing the Al-Mahara Journal, (2) involving students in managing the Al-Mahara Journal. In terms of other efforts obtained independently by students which are also inseparable from the efforts of the UIN SuKa Arabic Education study program, is holding scientific writing seminar activities.